2018
DOI: 10.1063/1.5027629
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the behaviors of ventilated supercavities in unsteady flow

Abstract: A systematic investigation of ventilated supercavitation behaviors in an unsteady flow is conducted using a high-speed water tunnel at the Saint Anthony Falls Laboratory. The cavity is generated with a forward facing model under varying ventilation rates and cavitator sizes. The unsteady flow is produced by a gust generator consisting of two hydrofoils flapping in unison with a varying angle of attack (AoA) and frequency (fg). The current experiment reveals five distinct cavity states, namely, the stable state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Correspondingly, although the cavity shape variation diminishes with reducing g , the cavity exhibits a more prominent closure variation associated with larger cavitation number fluctuation. Such trend of cavity closure variation under different g has also been reported in experiment (Shao et al 2018) and can be explained by the theoretical analysis in Karn et al (2016) and Karn et al (2015) which connect dimensionless differential pressure ∆ ' introduced in Section 3.2 to the cavitation number. Fig.…”
Section: Effect Of the Gust Frequencysupporting
confidence: 74%
See 3 more Smart Citations
“…Correspondingly, although the cavity shape variation diminishes with reducing g , the cavity exhibits a more prominent closure variation associated with larger cavitation number fluctuation. Such trend of cavity closure variation under different g has also been reported in experiment (Shao et al 2018) and can be explained by the theoretical analysis in Karn et al (2016) and Karn et al (2015) which connect dimensionless differential pressure ∆ ' introduced in Section 3.2 to the cavitation number. Fig.…”
Section: Effect Of the Gust Frequencysupporting
confidence: 74%
“…The numerical method is first validated through the experiments under specific steady and unsteady flow conditions. It has been shown that the simulation can capture the degree of cavity Finally, it is noteworthy that the present simulation is unable to capture the cavity length change due to shed-off of gas pocket near its closure region (i.e., pulsation of the cavity) which occurs under the cases of AOA8f1 and AOA8f5 in the experiments (Shao et al 2018). As discussed in (Shao et al 2018), the transition from the wavelike undulation to the cavity pulsation is a result of the bubble breakup near cavity closure induced by the instability of the gas-liquid interface.…”
Section: Summary and Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…They noted that a gust flow reduced the bubble condensation efficiency and an increase in the amplitude of the gust resulted in a slight monotonic increase in C q for the generation and collapse of a supercavity. Shao et al (2018) found that a supercavity was prone to becoming unstable and collapsing when its distortion exceeded its size as a result of the increase in f; further, increasing C q and the cavitator scale could inhibit the collapse of a supercavity. Due to the limits of experimental monitoring, it is relatively difficult to study the velocity distribution pattern of the entire gust flow field.…”
Section: Introductionmentioning
confidence: 99%